Assessment of Climate Change Impact on Highland Areas in Kastamonu, Turkey - Gur, Ezgi; Palta, Şahin; Özel, Halil Barış; Varol, Tuğrul; Sevik, Hakan; Cetin, Mehmet; Koçan, Nurhan (Elsevier BV, 2024)
This study aimed to assess the potential impact of global climate change on the highland areas of Kastamonu, a significant province in Turkey known for its numerous and varied highlands. The investigation focused on 59 selected highland locations within the region. Using the De Martonne climate classification, projections were made for four future periods (2040, 2060, 2080, and 2100) under two scenarios: SSPs 245 and SSPs 585. The outcomes of the study indicate that the highlands under scrutiny are susceptible to substantial effects from global climate change. Notably, these climatic alterations are expected to become evident within the next two decades, predominantly manifesting as a shift towards arid climate classifications. These shifts are anticipated to have a profound impact on the composition and diversity of species in the highland ecosystems. Based on the findings, it is advisable to consider interventions for the most climate-sensitive highland areas, such as facilitating the migration of species adapted to the new climate conditions and implementing initiatives to enhance species diversity. These efforts could help mitigate the potential loss of species and populations resulting from climate change.
Keywords: Kastamonu; De Martonne; Highland; Global Climate Change